Trade in Danubian Shaft-Hole Axes and the Introduction of Neolithic Economy in Denmark - Fischer, Anders (Journal of Danish Archaeology, 1982)
Trade in Danubian Shaft-Hole Axes and the Introduction of Neolithic Economy in Denmark.